P23 A Multidisciplinary Intervention to Reduce Antibiotic Duration in Lower Respiratory Tract Infections. (19th November 2012) - Murray, CD; Shaw, A; Fardon, TC; Smith, R; Schembri, S; Chalmers, JD
Abstract : Introduction: Prolonged courses of antibiotics in patients with lower respiratory tract infections (LRTI) are common and may contribute to antibiotic related side effects and antibiotic resistance. Prescribing shorter antibiotic courses may be equally effective and associated with fewer side effects. We developed and implemented a multidisciplinary intervention to reduce antibiotic duration in hospitalised patients with LRTI. Methods: This was a prospective before and after evaluation study conducted at Ninewells Hospital, Dundee from November 2011–May 2012 (pre-intervention) with post-intervention data collection during June and July. The intervention is scheduled to run until November 2012 but here we present the preliminary results. The multidisciplinary intervention consisted of automatic stop dates for antibiotics, protocolised antibiotic duration based on national guidelines and ward pharmacist feedback and reminders to stop antibiotics. Data recorded, in addition to length of antibiotic treatment, included underlying diagnosis and suspected antibiotic related side effects. Results: Pre-intervention, there were 281 patients (94 pneumonia, 121 exacerbation of COPD, 24 exacerbation of asthma and 42 LRTI/bronchitis or other chest infection). The mean duration of antibiotics was 8.3 days (range 1–21) with average by diagnosis of 9.3 days for CAP (range 5–21), 8.5 days for LRTI (3–16), 7.7 days for exacerbation of COPD (1–19) and 6.3 days for asthma (1–10). 31.3% of patients had a potential adverse effect of antibiotics. In preliminary data from the post intervention group, there were 97 patients (45 pneumonia, 40 exacerbation of COPD, 12 LRTI/bronchitis). The mean duration of antibiotic therapy was 6.7 days (range 1–14 days), p<0.0001 compared to pre-intervention. Post intervention duration of treatment for CAP was 7.0 days (1–14), p<0.0001 and for COPD patients was 6.4 days (5–14), p=0.0008 compared to pre-intervention. 16 (16.5%) patients post intervention had antibiotic related adverse effects, p=0.0005. There were 25 (8.9%) deaths pre-intervention and 7 (7.2%) deaths post-intervention, p=0.6 suggesting the reduction in antibiotic duration did not result in poorer clinical outcomes. Conclusion: This multidisciplinary intervention reduced antibiotic duration for lower respiratory tract infections and antibiotic related side-effects. This simple, effective intervention can be readily and quickly implemented into other clinical settings.